The wise man and the prophet Musa - Khan, Saniyasnain (Goodwordkidz New Delhi, 2003)
"The Wise Man and the Prophet Musa" from the Quran Stories for Little Hearts series narrates the story of Prophet Musa's encounter with a wise man, illustrating the importance of patience and understanding God's wisdom behind events. Through simple language and vivid storytelling, it teaches young readers valuable life lessons on faith and trust in God's plan.